Information Sharing in the Social Media Era: A User in African perspective - Masele, Juma James (University of Dar es Salaam Library Journal, 2022)
While the role of information for the functioning of any social system is enormous, individuals do not possess all the information that they require. It has to be shared. Using a systematic literature review this study presents an African perspective of information sharing in the era of social media. Electronic journals and reports written in English language and published from 2004 to 2021 were searched and reviewed. The study selection criteria flown directly from the review questions and was specified a priori. A Pareto analysis was used for summarizing, the vital and least important motivational factor for information sharing on social media platform. The study found that unlike the preceding era, social media makes information sharing ease, ubiquitous and convenient. Motivational factors to share information using social media included source credibility; networking motives, altruism, reciprocity, self-promotion, socializing, monetary rewards, perceptions of information quality and entertainment among others. Yet, Information sharing in Africa is contextually controlled by attitudes, perceptions, norms, values and belief systems inherent to local culture that in turn influence access, use and acceptance of shared information. Challenges revealed were mainly related to security; infrastructure, technical skills, resource related and inadequate supportive policies. The study concludes by proposing a conceptual model that explains information sharing in the African perspective.